MENINGKATAN KOMPTENSI PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK DI SEKOLAH DASAR NEGERI 015 RAMBAH HILIR - Ahmad Imam Syafi'i (STKIP Rokania Pasir Pangaraian, 2018)
This study aims to determine the appropriate steps in carrying out academic supervision so as to be able to improve the pedagogical competence of teachers, especially in the learning process which in turn will affect the improvement of the quality of education. The study was conducted in two cycles. Each cycle has different planning, implementation, observation and reflection. Research subject of the principal and teacher. The principal with an academic supervision act, while the 015 Elementary School teacher reaches Downstream as an object as well as the subject in providing academic supervision treatment. Data collection techniques through class supervision with the stages of supervising teachers in the learning process and observation of classroom learning, to record important events related to research, especially during the learning process takes place. The results showed that the teacher's ability to carry out the learning process experienced an increase in the percentage at each stage, from the first cycle reached an average of 62.50% (sufficient) and in the second cycle reached an average of 83.33% (very good). There was an increase in teacher's ability of 20.80% from cycle I. In detail there was a significant increase in the initial conditions of the school compared to the final condition in the second cycle. The accuracy of teachers entering the class increased by 48%, the use of learning media increased by 32%, varied methods increased by 31%, and learning strategies increased by 36%